Orthognatıc Surgery In Skeletal Class Iıı Cases (Case Reports) - Hüseyin Ölmez; Deniz Sağdıç; Osman Bengi; Onur Şengün (Galenos Yayinevi, 1994)
Treatment of dentofacial deformitiés mostly requires a combination of orthodontic and orthognatic surgery procedures. Application of such procedure helps to achieve normal jaw function, a functional occlusion, optimal facial esthetics and long-term stability. In this paper, 2 cases with skeletal Class HI malocclusions that treated by orthognatic surgical procedures, are presented.